The zebrafish (Danio rerio) is a relevant model for studying sex-specific effects of 17β-estradiol in the adult heart - Hein, Selina; Hassel, David; Kararigas, Georgios (International journal of molecular sciences, 2019)
Cardiovascular diseases are a major cause of morbidity and mortality, and there are significant sex differences therein. However, the underlying mechanisms are poorly understood. The steroid hormone 17β-estradiol (E2) is thought to play a major role in cardiovascular sex differences and to be protective, but this may not hold true for males. We aimed at assessing whether the zebrafish is an appropriate model for the study of E2 effects in the heart. We hypothesized that E2 regulates the cardiac contractility of adult zebrafish in a sex-specific manner. Male and female zebrafish were treated with vehicle (control) or E2 and the cardiac contractility was measured 0, 4, 7 and 14 days after treatment initiation using echocardiography. There was no significant effect on the heart rate by E2. Notably, there was a significant decrease in the ejection fraction of male zebrafish treated with E2 compared with controls. By contrast, there was no major difference in the ejection fraction between the two female groups. The dramatic effect in male zebrafish occurred as early as 4 days post treatment initiation. Although there was no significant difference in stroke volume and cardiac output between the two male groups, these were significantly higher in female zebrafish treated with E2 compared with controls. Gene expression analysis revealed that the levels of estrogen receptors were comparable among all groups. In conclusion, our data demonstrate that the adult zebrafish heart robustly responds to E2 and this occurs in a sex-specific manner. Given the benefits of using zebrafish as a model, new targets may be identified for the development of novel cardiovascular therapies for male and female patients. This would contribute towards the realization of personalized medicine.
Gesehen am 19.02.2020